PENGARUH KELENGKAPAN PRODUK, SUASANA TOKO DAN KENYAMANAN BERBELANJA TERHADAP KEPUTUSAN PEMBELIAN PADA MINIMARKET SULTHAN MART - Romzi, Muhammad Nizar Fauzi; Subagyo; Widodo, Moch. Wahyu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The intense competition in the retail business in the community is the background of this research. With the intense competition, retail business actors must be extra in influencing consumers to shop at their stores. The research was conducted at the Sulthan Mart Minimarket located in Mekikis Village, Purwoasri District, Kediri Regency. This research was conducted to find out how the influence of product completeness, store atmosphere and convenience of shopping on purchasing decisions. Respondents from this study were buyers at the Sulthan Mart Minimarket randomly with a total of 40 respondents. The methodin this study is quantitative which uses a questionnaire and is processed with SPSS v.23. The results of this study are product completeness partially has a significant effect on purchasing decisions, shop atmosphere partially has no significant effect on purchasing decisions, shopping convenience partially has a significant effect on purchasing decisions. Product completeness, store atmosphere, and convenience of shopping together or simultaneously have a significant effect on purchasing decisions